PENGEMBANGAN MEDIA DIGITAL BERBASIS EDPUZZLE UNTUK MEMPERKUAT MOTIVASI BELAJAR SISWA SEKOLAH DASAR (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2025)
This article discusses the use of Edpuzzle-based digital media as an innovative approach to strengthening elementary students’ learning motivation. In many classrooms, learning activities are still dominated by teacher explanations and textbook-based instruction, which often limits students’ engagement and enthusiasm. This study applies interactive video media supported by Edpuzzle to create a more dynamic and student-centered learning environment. Data were collected through classroom observations and students’ responses after the learning activities. The findings indicate that the use of interactive digital videos encourages students to pay more attention, participate more actively, and showgreater interest in the learning process. The combination of visual content andembedded questions helps students stay focused and emotionally involved inclassroom activities. Therefore, Edpuzzle-based digital media can be considered aneffective pedagogical innovation for strengthening students’ learning motivation in elementary education.